Bilateral acute anterior uveitis and iris atrophy caused by moxifloxacin. Issue 6 (30th June 2020) - Hui, Benjamin Tsun Kiu; Capewell, Nicholas; Ansari, Yousuf; Liu, Xiaoxuan
Abstract : A 56-year-old paramedic was admitted to hospital and treated for severe pneumonia. Shortly after initiating antibiotic treatment (including moxifloxacin), he developed bilaterally painful eyes and was diagnosed with bilateral acute anterior uveitis (AAU). Three years later, he was referred to the ophthalmology clinic with bilateral iris transillumination suggesting iris atrophy and limited pupillary dilation, indicating iris sphincter muscle paralysis. AAU typically presents unilaterally. An onset of bilateral AAU is unusual and warrants investigation for underlying systemic cause. The fluoroquinolone moxifloxacin has been reported in a limited number of cases as a causative agent of bilateral AAU and iris atrophy. This case provides additional supporting evidence that moxifloxacin may cause degradation of collagen and iris muscle in the eye, as well as elsewhere in the body, such as in blood vessels. Additionally, we present novel anterior segment ocular imaging (using optical coherence tomography) demonstrating the ability to detect iris atrophy using non-invasive imaging.